(untitled) (REMUNOM, 2025)
Introduction: Aromatherapy and massage therapy are anti-stress resources and can beneficially influence sleep quality. Objective: To evaluate the effects of massage with and without aromatherapy on the sleep quality of medical students. Methodology: The sample consisted of 10 medical students, submitted to 2 sessions per week for two months and divided into G1 - Students undergoing massage therapy with neutral oil (n = 5) and G2 - Students undergoing aromatherapy massage therapy (n = 5). The division was based on the application of the Pittsburgh Sleep Quality Index (PSQI). The data collection instruments were used: 1) Sociodemographic Questionnaire (QSD), 2) Epworth Sleepiness Scale (ESS-BR) and 3) PSQI. Results: The QSD data showed that the population studied does not have lifestyle habits that enhance poor sleep quality, such as smoking, alcoholism, obesity or diseases being treated. However, the students reported using their smartphone (cell phone) frequently before going to sleep. The findings of the application before and after the sessions, obtained by the PSQI, showed that both students submitted to massage therapy with the application of neutral oil, and the students submitted to massage therapy with the application of neutral oil plus lavender essential oil, had an increase of one sleep time. The ESS-BR data showed that no student has severe sleepiness. Conclusion: The effects of massage with and without aromatherapy provided improvements in the sleep quality of the students participating in this study, with no differences in the findings through aromatherapy.